Optimized isolation and purification of native glycoprotein B from herpes simplex virus 1: a streamlined approach - Mohammad Yasaghi; Ahad Yamchi; Alijan Tabarraei; Sara Salari; Abdolvahab Moradi; Seyedeh Delafruz Hosseini (Iranian Journal of Microbiology)
Background and Objectives: Viral membrane glycoproteins are essential for host cell recognition, membrane fusion and immune evasion, making them critical targets for antiviral therapies and vaccine development. However, their isolation in native conformation is challenging due to structural complexity and limitations of conventional purification methods. The aim of current study was to develop a cost-effective, reproducible method for the isolation and purification of glycoprotein B (gB) from Herpes Simplex Virus type 1 (HSV-1) while maintaining its native conformation for functional and interaction studies. Materials and Methods: HSV-1 particles were concentrated via ultracentrifugation and membrane proteins were extracted using a modified protocol of the Mem-PER™ Plus Membrane Protein Extraction Kit. Native PAGE with a 4-8% gradient gel was employed to isolate multimeric gB (~300 kDa), followed by electroelution to extract the protein from the gel. The purity and integrity of gB were validated using SDS-PAGE and Western blot analysis. Results: The method successfully isolated glycoprotein B in its native multimeric form with high purity and adequate concentration (0.157 mg/mL). The pH of the native gel (8.3) and the high molecular weight of gB facilitated separation from other viral surface proteins. SDS-PAGE and Western blot confirmed the specificity and structural integrity of the purified protein. Conclusion: This study introduces a cost-effective and reliable method for isolating viral glycoproteins in their native conformation. The approach offers significant advantages over traditional chromatography-based techniques, making it ideal for research-scale applications, including functional and interaction studies.